Justin, `philosophe' chrétien et les `Mémoires des Apôtres qui sont appelés Evangiles' - Aragione, Gabriella (Apocrypha, 2004)
This paper investigates the reasons why Justin chose to name the Gospels « Memoirs ». After a brief survey of past scholarship on this issue, it will be shown that in Justin's time the literary genre of Memoirs was well attested and that it presented several features similar to those of the Gospel narratives. Justin, who was at the head of a school of Christian ``philosophy'', made use of a title which could be grasped as well by his Christian addresses - who could have seen a reference to the testimony of the apostles - as by his pagan addresses - who could have seen a similitude with the Memoirs of a philosophical teacher.